Publisher Correction: Absence of NKG2D ligands defines leukaemia stem cells and mediates their immune evasion - Paczulla, Anna Maria; Raffel, Simon; Nievergall, Eva; Lutz, Christoph; Trumpp, Andreas (Nature, 2019)
An Amendment to this paper has been published and can be accessed via a link at the top of the paper.